FLORICULTURE. THE IMPORTANCE OF SOME REPRESENTATIVES OF THE CARNATION FAMILY (CARYOPHYLLACEAE) (Proceedings of International Educators Conference, 2024)
This article presents information about the emergence of the field of flowering, the composition, importance of Representatives of the Carnation family (Caryophyllaceae).